Is the Capsaicin 179 mg (8% w/w) Cutaneous Patch an Appropriate Treatment Option for Older Patients with Peripheral Neuropathic Pain? - Pickering G; Engelen S; Stupar M; Ganry H; Eerdekens M (Journal of Pain Research, 2024)
Gisèle Pickering,1 Sylvia Engelen,2 Maria Stupar,2 Hervé Ganry,3 Mariëlle Eerdekens2 1Faculty of Medicine Inserm 1107, Clinical Pharmacology Centre, CPC/CIC Inserm 1405 University Hospital, Clermont-Ferrand, France; 2Grünenthal GmbH, Aachen, Germany; 3Hergan Consulting 4U, Amiens, 80000, FranceCorrespondence: Mariëlle Eerdekens, Grünenthal GmbH, Zieglerstrasse 6, Aachen, 52078, Germany, Tel +492415 691090, Email Marielle.Eerdekens@grunenthal.comIntroduction: Capsaicin 179 mg (8% weight per weight) cutaneous patch (“capsaicin patch”) is a recommended topical treatment for peripheral neuropathic pain (PNP). In older patients, topical treatments may be preferred over systemic treatments, but data specific to the older population are scarce.Methods: We conducted pooled analyses of multiple clinical trials to evaluate efficacy and safety of capsaicin patch in older patients. The analysis of efficacy included four randomized, double-blind, 12-week studies with similar trial design comparing a single treatment of capsaicin 179 mg cutaneous patch vs low-dose control patch in post-herpetic neuralgia. For the safety evaluation, data were pooled from 18 interventional studies in which capsaicin patch was used in PNP with varying etiologies.Results: Capsaicin patch had similar analgesic efficacy in elderly (n=582) and non-elderly patients (n=545) in terms of change from baseline to 2– 12 weeks in the 11-point numeric pain rating scale (NPRS) score for average pain over the previous 24 hours. In both age groups, decrease in NPRS score was significantly greater with capsaicin patch vs control. Older patients treated with capsaicin patch were significantly more likely than those in the control group to achieve responder status (ie mean decrease in NPRS score from baseline to week 2– 12 of at least 30% or ≥ 2 points): 36.1% vs 27.1% (odds ratio [OR] [95% CI] 1.52 [1.06, 2.18]; P=0.0231) and 33.1% vs 20.9% (OR [95% CI] 1.90 [1.30, 2.78]; P=0.0009) for active treatment vs control group, respectively. Similar proportions of non-elderly patients (n=2,311) and elderly patients (n=537) treated with capsaicin patch experienced treatment-emergent adverse events (TEAEs) (81.6% and 78.1%, respectively) and serious TEAEs (8.2% and 7.2%), with application-site reactions the most common TEAEs in both groups.Conclusion: The capsaicin patch was equally efficacious and well tolerated in older patients as in younger patients.Plain language summary: Peripheral neuropathic pain is a common challenge among the elderly, yet effective treatments for this age group remain underexplored. This research focuses on the use of a high-concentration capsaicin patch, a specialized treatment for this type of pain. The patch, which is applied directly to the affected skin area, has been shown to reduce pain significantly for up to 12 weeks. This analysis of multiple clinical trials showed that the high-concentration capsaicin patch significantly reduced pain intensity and was well tolerated in older patients with peripheral neuropathic pain.Keywords: capsaicin patch, elderly, peripheral neuropathic pain, pooled analysis, topical treatment